2018
DOI: 10.1111/joa.12889
|View full text |Cite
|
Sign up to set email alerts
|

Autism‐linked CHD gene expression patterns during development predict multi‐organ disease phenotypes

Abstract: Recent large‐scale exome sequencing studies have identified mutations in several members of the CHD (Chromodomain Helicase DNA‐binding protein) gene family in neurodevelopmental disorders. Mutations in the CHD2 gene have been linked to developmental delay, intellectual disability, autism and seizures, CHD8 mutations to autism and intellectual disability, whereas haploinsufficiency of CHD7 is associated with executive dysfunction and intellectual disability. In addition to these neurodevelopmental features, a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 99 publications
1
14
0
Order By: Relevance
“…In addition, 50% of Chd8 neo/− embryos showed unilateral anopthalmia (Additional file 1 : Fig. S2H), in agreement with strong Chd8 expression in the developing eye [ 35 ]. Taken together, these data suggested that brain growth responds to reductions in CHD8 levels in a non-linear manner, with heterozygotes and mild hypomorphs exhibiting brain overgrowth, and severe hypomorphs presenting with brain hypoplasia.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, 50% of Chd8 neo/− embryos showed unilateral anopthalmia (Additional file 1 : Fig. S2H), in agreement with strong Chd8 expression in the developing eye [ 35 ]. Taken together, these data suggested that brain growth responds to reductions in CHD8 levels in a non-linear manner, with heterozygotes and mild hypomorphs exhibiting brain overgrowth, and severe hypomorphs presenting with brain hypoplasia.…”
Section: Resultsmentioning
confidence: 60%
“…Chd8 neo/neo mice exhibited a significant reduction in postnatal survival (Table 1 ). As CHD8 is expressed in multiple tissues during development [ 35 ], this postnatal lethality is likely a consequence of congenital defects affecting essential organs.…”
Section: Resultsmentioning
confidence: 99%
“…Both neuronal and glial cells are implicated in ASD pathobiology (Ballas et al, 2009;Derecki et al, 2012;Gupta et al, 2014;Kasah et al, 2018;Morgan et al, 2012;Morgan et al, 2010;Suzuki et al, 2013;Voineagu et al, 2011). The XP-broad network is expressed across cell types, while the XP-specific network is enriched in neuronal cells.…”
Section: Non-neuronal Cells Harbor Dysregulated Transcription In Broamentioning
confidence: 99%
“…Although valuable, such models ignore potential impacts of ASD genetics in other cellular or developmental contexts. For example, rASD genes are linked to biological processes related to non-neuronal cell types including microglia, astrocytes, and leukocytes (Ballas et al, 2009;Derecki et al, 2012;Gupta et al, 2014;Kasah et al, 2018;Pramparo et al, 2015;Suzuki et al, 2013;Voineagu et al, 2011). Likewise, genetic variants related to brain processes, diseases, and disorders can modulate gene expression in cell types other than neurons and tissues other than brain (Lin et al, 2018;Lombardo et al, 2018;Pardinas et al, 2018;Wright et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chromodomain helicase DNA-binding protein 8 (CHD8) is a member of ATP-dependent chromatin remodeling protein in the CHD family [19]. CHD8 is related to the development of autism [20,21], and involved in embryonic development and apoptosis of vascular smooth muscle cells [19,22]. However, the function of CHD8 in myocardial I/R injury and H/R is not known yet.…”
Section: Introductionmentioning
confidence: 99%